Establishing a core collection from the integration of morpho (Revista Ciência Agronômica, 2015)
The aim of this study was to establish and compare, as to their representativeness, core collections obtainedfrom quantitative data, multicategoric, molecular and collections that covering all this information simultaneously.Ten subcollections were established from 67 tomato accessions of the Germplasm Bank of the Universidade Federalde Viçosa (BGH-UFV), characterized according to 19 quantitative traits, 30 multicategoric characters, 52 ISSR lociand to the reaction to three pathogens. These subcollections were defined by the combination of the nature of datacollected and the sampling rate. The COD-20 subcollection stood out in 20% intensity of sampling by has higher rates ofcoincidence amplitude followed by more appropriate values of variance. At 30% intensity, subcollection MOL-30 was asefficient as the subcollection COD-30 when considering only the rates of coincidence of the amplitude and the variances.However, the graphical analysis of the variability showed a slight superiority of subcollection COD-30 in maintainingthe variability, especially regarding multicategoric characters. So whenever data from different sources are available,should be prioritized the establishment of core collections from the integration of these data, since these were morerepresentative when the amplitude coefficient, variance, and retention index of variability, are regarded simultaneously.